2020
DOI: 10.1093/braincomms/fcaa182
|View full text |Cite
|
Sign up to set email alerts
|

Delta-gamma phase-amplitude coupling as a biomarker of postictal generalized EEG suppression

Abstract: Phase-amplitude coupling analysis shows that a state of postictal generalized EEG suppression has increased delta-gamma coupling. These coupling features, used with an unsupervised hidden Markov model, reliably differentiated four substates in seizure episodes. A sudden unexpected death in epilepsy case study showed coupling activity similar to a postictal state. Postictal generalized EEG suppression is the state of suppression of electrical activity at the end of a seizure. Prolongation of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…In general, these changes in neuronal oscillations were consistent in the postictal suppression state, regardless of whether the suppression was generalized or not across channels. Then, it was also suggested that very high frequency oscillations (600–2000 Hz) could be combined with low delta as an additional biomarker for postictal states [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these changes in neuronal oscillations were consistent in the postictal suppression state, regardless of whether the suppression was generalized or not across channels. Then, it was also suggested that very high frequency oscillations (600–2000 Hz) could be combined with low delta as an additional biomarker for postictal states [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the same test, we also compared the percentage of animals with seizures during the treatment period in LEV-and saline-treated groups. After having tested for normality of distribution (Shapiro-Wilk test), data on seizure duration were analyzed by a 2-way (Treatments: LEV, SALINE) × 21 (Time Intervals expressed in days: 36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56) repeated measures ANOVA. Post hoc comparisons, when appropriated, were done using a multiple comparison test (Holm-Šidák).…”
Section: Statisticsmentioning
confidence: 99%
“…After 2 weeks of tUS stimulation, the theta-gamma coupling in Tg/Stim + in day 14 increased signi cantly in comparison with Tg/Stim + at baseline. Delta-gamma coupling also considered as a biomarker for the evaluation of generalized EEG suppression as well as network activity [41]. Our results showed an exaggeration of delta-gamma coupling in Tg/Stim + day 14 in comparison with Tg/Stim + at baseline.…”
Section: Functional Improvement Could Be Achieved By Tusmentioning
confidence: 52%
“…2013 ; Zhang et al. 2017 ; Grigorovsky et al. 2020 ) that matched pre- and postdischarge signals as well as the onset, middle, and offset epochs of regional discharges ( Grigorovsky et al.…”
Section: Resultsmentioning
confidence: 90%
“…PAC strength was assessed using the algorithm by Tort et al. (2010) where phase and amplitude of different frequency bands were obtained via the complex wavelet Morlet wavelet transform using a mother wavelet with a central frequency of 0.8125 Hz and bandwidth of 5 Hz previously used on human EEG data ( Grigorovsky et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%